2020
DOI: 10.1038/s41598-020-71226-0
|View full text |Cite
|
Sign up to set email alerts
|

Bats as putative Zaire ebolavirus reservoir hosts and their habitat suitability in Africa

Abstract: the genus Ebolavirus comprises some of the deadliest viruses for primates and humans and associated disease outbreaks are increasing in Africa. Different evidence suggests that bats are putative reservoir hosts and play a major role in the transmission cycle of these filoviruses. Thus, detailed knowledge about their distribution might improve risk estimations of where future disease outbreaks might occur. A MaxEnt niche modelling approach based on climatic variables and land cover was used to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
1
33
0
2
Order By: Relevance
“…In addition, although bats are reservoirs of several viruses that have been responsible for serious outbreaks, models have shown that viruses harbored by bats are no more likely to be zoonotic than viruses that are harbored or transmitted by rodents or other hosts [ 19 ]. For some viruses in the genus Ebolavirus , bats are the presumptive main reservoir, but have yet to be definitively confirmed [ 34 , 35 , 36 , 37 ].…”
Section: What Biological Strategies Have Evolved That Allow Rna Viruses To Reside In Bats and Rodents?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although bats are reservoirs of several viruses that have been responsible for serious outbreaks, models have shown that viruses harbored by bats are no more likely to be zoonotic than viruses that are harbored or transmitted by rodents or other hosts [ 19 ]. For some viruses in the genus Ebolavirus , bats are the presumptive main reservoir, but have yet to be definitively confirmed [ 34 , 35 , 36 , 37 ].…”
Section: What Biological Strategies Have Evolved That Allow Rna Viruses To Reside In Bats and Rodents?mentioning
confidence: 99%
“…Extensive searches have been conducted to identify the reservoir, but it remains elusive [ 216 , 217 ]. Bats have been proposed to harbor the viruses but have not been proven to be the reservoir [ 34 , 37 ]. While the reservoir for the virus has yet to be identified, numerous outbreaks have occurred following humans handling animals such as primates (chimpanzees and gorillas) and antelopes (duikers) and their carcasses [ 218 , 219 , 220 ].…”
Section: How Do Viruses Spillover From Bats or Rodents To Humans?mentioning
confidence: 99%
“…Shown are the enzootic cycles (i.e., the predominant, long-term natural host reservoirs of the virus and transmission vectors) and epizootic cycles (i.e., spillover of the virus into other susceptible species and/or alternative transmission vectors). The main natural host reservoir of Ebola virus is thought to be certain species of Old World fruit bats, but the virus is capable of transmission to many other mammalian species [ 1 , 7 , 8 , 9 , 10 ]. The natural host reservoir of VSV is thought to be mainly small rodents, such as deer mice, with sandflies acting as transmission vectors; however, VSV is also capable of infecting many other animal species and can be transmitted via other insects [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Figurementioning
confidence: 99%
“…EVD is a zoonotic disease, with EBOV believed to be transmitted to human index cases through close contact with bodily fluids of infected, rainforest-dwelling mammals. Prevailing evidence suggests that fruit bats are the predominant natural host reservoir of EBOV, with other species such as rodents, porcupines, pigs, dogs, non-human primates, and also humans merely serving as accidental spillover hosts ( Figure 1 a) [ 1 , 7 , 8 , 9 , 10 ]. However, once the virus has successfully infected an index patient, EBOV readily spreads human to human by direct contact with bodily fluids/tissues of EVD patients or with fomites contaminated with such infectious materials [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit bats, including Hypsignathus monstrosus, Epomops franqueti, and Myonycteris torquate have also been suggested as potential reservoirs for Zaire Ebolavirus [12,17]. In addition to these zoonotic viral infections, bats also serve as potential reservoirs for other viruses responsible for infections in humans that include Nipah, Hendra, Marburg, Hepadna (able to infect human hepatocytes), and Lyssa viruses etc.…”
Section: Introductionmentioning
confidence: 99%